2021
DOI: 10.1080/10615806.2021.1913489
|View full text |Cite
|
Sign up to set email alerts
|

Are we seeing “eye to eye” on qualitative job insecurity in healthcare? Employee–teammates perceptual (in)congruence and individual well-being

Abstract: Background: In healthcare, employees are exposed to continuous change when new methods are implemented to optimize care. Such changes may result in qualitative job insecurity (QJI), i.e., a fear concerning the potential loss of important job features. QJI is an individual experience; however, it may be shared within a team to a varying extent. This study examines how QJI perceptual (in)congruence between individuals and their teammates relates to individuals' well-being. Method: Healthcare employees (N = 305) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…This way we also complement prior research that has focused on the mediation mechanism of basic need satisfaction, as a form of motivation, in the relationship between qualitative job insecurity and employee performance-related indicators (Stynen et al, 2015; Van den Broeck et al, 2014). Recent contributions (Long et al, 2021; Roczniewska and Richter, 2021) demonstrate the increasing interest in the relationship between qualitative job insecurity and employee motivation or similar concepts; yet, thus far, motivation has been mostly studied as an outcome of qualitative job insecurity. Adding to the still limited evidence on employee motivation as a moderator, our findings indicate that employee motivational type is a meaningful boundary condition that co-shapes the effect of qualitative job insecurity on ERBs.…”
Section: Discussionmentioning
confidence: 99%
“…This way we also complement prior research that has focused on the mediation mechanism of basic need satisfaction, as a form of motivation, in the relationship between qualitative job insecurity and employee performance-related indicators (Stynen et al, 2015; Van den Broeck et al, 2014). Recent contributions (Long et al, 2021; Roczniewska and Richter, 2021) demonstrate the increasing interest in the relationship between qualitative job insecurity and employee motivation or similar concepts; yet, thus far, motivation has been mostly studied as an outcome of qualitative job insecurity. Adding to the still limited evidence on employee motivation as a moderator, our findings indicate that employee motivational type is a meaningful boundary condition that co-shapes the effect of qualitative job insecurity on ERBs.…”
Section: Discussionmentioning
confidence: 99%
“…Job insecurity factors were found to affect not only mental illness, but also physiological variables, such as physical symptoms and various physical fatigue [19,20]. In addition, it is confirmed that job insecurity has a negative relationship with psychological well-being, such as job enthusiasm and life satisfaction [21][22][23][24]. In this research, in the field of hotel organization management, well-being was selected, in which the job insecurity factor is a result variable.…”
Section: Job Insecurity and Psychological Well-beingmentioning
confidence: 74%